1997
DOI: 10.1359/jbmr.1997.12.1.152
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral Deformities and Functional Impairment in Men and Women

Abstract: The objective of this study was to assess the prevalence and health effects of vertebral deformities in men and women. The study was carried out as part of the cross-sectional baseline phase of The Rotterdam Study, a prospective population-based cohort study of residents aged 55 years or over of a district of Rotterdam, The Netherlands. The prevalence of vertebral deformities according to a modification of the Eastell method and concomitant functional impairment were assessed in a random sample of 750 men and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
150
3
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(167 citation statements)
references
References 23 publications
(16 reference statements)
11
150
3
3
Order By: Relevance
“…All women except four, who wanted to take part, had however not been investigated earlier for their height shortening and had also no current history of back pain leading to medical examination, why the group was valuable to investigate. The prevalence of spinal fractures in our material was 45% which seems high compared to other studies where prevalence values from two to 39% have been demonstrated in men and women in different countries ( 1,8,(12)(13)(14)(15)(16). However, those studies were prevalence investigations in contrast to our trial comprising women with known height loss.…”
Section: Discussioncontrasting
confidence: 61%
“…All women except four, who wanted to take part, had however not been investigated earlier for their height shortening and had also no current history of back pain leading to medical examination, why the group was valuable to investigate. The prevalence of spinal fractures in our material was 45% which seems high compared to other studies where prevalence values from two to 39% have been demonstrated in men and women in different countries ( 1,8,(12)(13)(14)(15)(16). However, those studies were prevalence investigations in contrast to our trial comprising women with known height loss.…”
Section: Discussioncontrasting
confidence: 61%
“…25 In those with SCI, 55% (11 of the 20 subjects) had mild to moderate DJD and 25% (5 of the 20 subjects) had severe DJD of the L-spine. In contrast, in the control group, 40% (6 of the 15 subjects) had mild DJD and none had moderate or severe DJD of the L-spine.…”
Section: Discussionmentioning
confidence: 95%
“…Visual assessment of vertebral fracture on plain radiographs is notoriously subjective [3] so semi-quantitative and quantitative schemes have been developed to measure vertebral body deformity as a more reproducible indicator of fracture [1,2,4,5].…”
Section: Introductionmentioning
confidence: 99%